High prevalence of morphometric vertebral fractures opportunistically detected on thoracic radiograms in patients with non-functioning pituitary adenoma - Frara, Stefano; Uygur, Meliha Melin; Bolamperti, Filippo; di Filippo, Luigi; Doga, Mauro; Ferrari, Francesca; Losa, Marco; Mortini, Pietro; Giustina, Andrea (Pituitary, 2024)
Purpose Vertebral fractures (VFs), the hallmark of skeletal fragility, have been reported as an emerging complication in patients with pituitary diseases associated with hormonal excess and/or deficiency, independently from bone mineral density. Non-functioning pituitary adenoma (NFPA) is amongst the most frequent pituitary adenomas; however, skeletal health in this context has never been investigated. We aimed at assessing the prevalence and the determinants of morphometric VFs in patients with NFPA. Methods We enrolled 156 patients (79 M/77F, mean age 55.75 ± 12.94 years) at admission in Neurosurgery Unit before trans-sphenoidal surgery and compared them with an age and sex-matched control group of subjects with neither history/risk factors for secondary osteoporosis nor pituitary disorders. We performed a vertebral morphometric evaluation of the thoracic spine on pre-operative X-ray images (MTRx) and collected biochemical, demographic, and clinical data from the entire cohort. Results The prevalence of thoracic VFs in patients with NFPA was significantly higher than the control group (26.3% vs. 10.3%; p < 0.001). In the NFPA group, 20 patients (48.8% of the fractured patients) showed multiple VFs, 14 (34.1% of them) showed moderate/severe VFs. Patients with VFs were significantly older and had lower serum free triiodothyronine (fT3) levels than non-fractured ones (p = 0.002 and p = 0.004; respectively). The prevalence of secondary male hypogonadism was higher among men with VFs as compared to those with no VFs (72% vs. 48.1%; p = 0.047). Consistently, total testosterone levels in males were significantly lower in fractured patients than in non-fractured ones (p = 0.02). The prevalence of gonadotroph adenomas was significantly higher among patients with VFs (p = 0.02). In multiple logistic regression analysis, older age and lower serum fT3 levels were independent factors predicting the risk for VFs. Conclusions For the first time, we reported a high prevalence of thoracic radiological VFs in patients with NFPAs. Our data should prompt clinicians to proceed with a clinical bone fragility evaluation already during the diagnostic work-up, particularly in those with concomitant hypogonadism, or in those with older age and/or with lower fT3.